Periode Pelatihan Fisik untuk Atlet Elit: Konsep Saat Ini dan Arah Masa Depan - Sahabuddin (PT. PENERBIT TIGA MUTIARA, 2025)
Physical training periodization is a scientific approach aimed at systematically regulating training load, volume, and intensity to achieve peak performance in elite athletes while minimizing the risk of injury. This study reviews 45 scientific articles published within the last ten years, covering periodization models, physiological responses to training, and the integration of technology in athlete development processes. The findings indicate that block periodization and non-linear periodization are the two most effective approaches, shown to enhance aerobic capacity by up to 10% and muscle strength by approximately 8% in high-level athletes. Additionally, the use of monitoring technologies such as Heart Rate Variability (HRV) and Global Positioning System (GPS) contributes significantly to real-time adjustments in training programs, enabling coaches to respond more accurately to athletes’ physiological conditions and prevent overtraining. However, challenges remain in implementing these technologies in sports with limited resources and due to a lack of long-term studies on the effectiveness of technology-based periodization. These findings emphasize the importance of individualized, data-driven approaches in designing training programs that not only improve performance but also sustain athletes’ careers. By integrating classical periodization principles with modern technology, training programs can be developed to be more adaptive, precise, and contextually tailored to individual needs. In conclusion, modern, responsive periodization supported by advanced technology is a crucial element in creating elite athlete development systems that are not only globally competitive but also focused on long-term health and performance.